Evaluation of a Novel Mucosal Administered Subunit Vaccine on Colostrum IgA and Serum IgG in Sows and Control of Enterotoxigenic Escherichia coli in Neonatal and Weanling Piglets: Proof of Concept - Jabif, Maria Fernanda; Gumina, Emanuel; Hall, Jeffrey W.; Hernandez-Velasco, Xochitl; Layton, Sherry (Frontiers in Veterinary Science, 2021)
The purpose of the present study was to evaluate the ability of a novel experimental subunit vaccine (ESV), induce colostrum IgA and serum IgG in sows, and to control enterotoxigenic Escherichia coli (ETEC) disease in neonatal and weanling piglets. The vaccine was tested in three experiments. Exp 1 consisted of two independent trials. In each trial, 20 pregnant sows/groups were vaccinated intramuscularly (IM) with a commercial E. coli vaccine or intranasally with ESV at weeks 11 and 13 of pregnancy. Blood and serum samples were obtained within 12 hours post-partum. In Exp 1, intranasal vaccination with ESV significantly increased the sample-to-positive (S/P) ratio of secretory IgA in the colostrum of sows (P<0.01, trial 1; P<0.05, trial 2) compared to the IM vaccine. In Exp 2, twenty-five 3-day old piglets were randomly allocated into two groups, control (n=13) or ESV (n=12) and were oral gavaged with the respective treatments on days 3 and 14 of life. On days 17-19, all piglets were challenged using a mixed ETEC culture via oral gavage. Within 72 hours, all control group animals developed disease consistent with colibacillosis. Conversely, the ESV treated group remained disease free over the 7-day observation period and had significant increases in body weight gain compared to the control group piglets. In Exp 3, thirty 28-day old piglets were randomly allocated, control (n=15) or ESV (n=15), and on days 33 and 43 of life, piglets were either given by oral gavage 2.0 mL saline (control group) or 2.0 mL ESV. At days 46 and 47 of life, all pigs were challenged with a mixed culture of ETEC and observed for clinical signs of disease. Results of Exp 3 were similar to those observed in Exp 2. This study indicates the ESV can induce better levels of colostrum secretory IgA in pregnant sows than IM vaccination, which may be protective to neonatal piglets. Further, the vaccine can protect piglets as early as 3 days of age from an ETEC infection. Importantly, the data suggest a single vaccine could be used across the farrowing, suckling, and weaning program to protect against pathogenic E. coli.